Perencanaan Penempatan Engine Pada Mobil Minimalis Roda Tiga - Pradita Eko Kuncahyo; Tri Andi Setiawan; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Three wheels cars has a minimalist concept that is comfortable and simple. By utilizing theprinciple of tilting trike system which makes access easier in all fields. Of course the car is designedto be comfortable and safe when driving. For that purpose this research is made plotting the rightengine placement to be safe and stay comfortable to drive. And this research is to find out how muchvibration generated by the engine is still safe for the rider or not by using vibration meter.